Full mobile agent interoperability in an IEEE-FIPA context - Cucurull, J.; Martí, R.; Navarro-Arribas, G.; Robles, S.; Borrell, J. (The Journal of systems and software, 2009)
The existence of heterogeneous mobile agent systems hinders the interoperability of mobile agents. Several solutions exist, but they are limited in some aspects. This article proposes a full interoperability solution, in the context of the IEEE-FIPA agent standards, composed of three parts. The first part is a simple language-independent agent interface that enables agents to visit locations with different types of middlewares. The second part is a set of design models for the middlewares to support agents developed for different programming languages and architectures. And the third part is a method based on agents with multiple codes and a common agent data encoding mechanism to enable interoperability between middlewares that do not support the same programming languages. Furthermore two agent interoperability implementations, and its corresponding performance comparison, carried out over the JADE and AgentScape agent middlewares are presented.